2022
DOI: 10.3390/nu14061238
|View full text |Cite
|
Sign up to set email alerts
|

Association of Frailty Status and Dietary Patterns in a Nationally Representative Sample of United States Adults with Olfactory Dysfunction

Abstract: Background: Olfactory dysfunction (OD) is a strong, independent predictor of frailty and mortality risk. This study evaluated the association of dietary patterns and frailty status in older adults with OD. Methods: This cross-sectional study utilized the 2013–2014 National Health and Nutrition Examination Survey. Dietary patterns (DPs) characteristic of OD were derived using exploratory factor analysis (EFA). Multiple logistic regressions adjusted for demographics and frailty risk factors assessed the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…60,61 Disruptions in the ability to smell may represent a set of risks uniquely poised to worsen the outcomes of survivors of HNC, including dietary changes and weight loss in individuals who have inherently decreased oral intake secondary to their pathology, decreased social interactions, and an increased risk of depression and anxiety. 29,[62][63][64][65] Pre-existing depression and depression diagnosed after HNC diagnosis are associated with a greater hazard of both cancer-specific and allcause mortality. 66 Several robust prospective studies have demonstrated a link between mental disorders, including major depressive disorder, with increased risk of age-related medical illnesses, such as cardiovascular disease, type 2 diabetes, metabolic syndrome, and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60,61 Disruptions in the ability to smell may represent a set of risks uniquely poised to worsen the outcomes of survivors of HNC, including dietary changes and weight loss in individuals who have inherently decreased oral intake secondary to their pathology, decreased social interactions, and an increased risk of depression and anxiety. 29,[62][63][64][65] Pre-existing depression and depression diagnosed after HNC diagnosis are associated with a greater hazard of both cancer-specific and allcause mortality. 66 Several robust prospective studies have demonstrated a link between mental disorders, including major depressive disorder, with increased risk of age-related medical illnesses, such as cardiovascular disease, type 2 diabetes, metabolic syndrome, and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions in the ability to smell may represent a set of risks uniquely poised to worsen the outcomes of survivors of HNC, including dietary changes and weight loss in individuals who have inherently decreased oral intake secondary to their pathology, decreased social interactions, and an increased risk of depression and anxiety . Pre-existing depression and depression diagnosed after HNC diagnosis are associated with a greater hazard of both cancer-specific and all-cause mortality .…”
Section: Discussionmentioning
confidence: 99%
“…1 Though the exact mechanism for this relationship remains unclear, prior studies have linked OD with neurodegenerative diseases, poor nutrition, diminished danger warning, and frailty. 2,3 This suggests that OD may be reflective of pathophysiologic changes associated with overall reduced physiologic reserve. Importantly, therapeutic interventions for OD are limited, and the potential benefits of OD-targeted therapies are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence has demonstrated that olfactory dysfunction (OD) is predictive of overall mortality 1 . Though the exact mechanism for this relationship remains unclear, prior studies have linked OD with neurodegenerative diseases, poor nutrition, diminished danger warning, and frailty 2,3 . This suggests that OD may be reflective of pathophysiologic changes associated with overall reduced physiologic reserve.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature suggests that olfactory and gustatory dysfunctions are early indicators of both frailty and mortality [12][13][14]. In this respect, the study by Vohra et al [15] evaluated the association between dietary patterns and frailty status in older adults with olfactory dysfunction, showing that dietary patterns high in protein/selenium and b-carotene/vitamin A were associated with a lower prevalence of frailty in adults with olfactory dysfunction. Instead, no dietary pattern was associated with any measure of frailty in normosmic people.…”
mentioning
confidence: 99%